Menstrual problems among adolescent girls in Thiruvananthapuram district - Beevi P., Nazeema; L., Manju; S, Anil Bindhu; Haran, Jeesha C.; Jose, Regi (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescence is a transitional stage extending from 10-19 years characterized by rapid physical, mental and sexual changes. It is also characterized by hormonal changes. As girls attain puberty at this age, they have various problems associated with menstruation. Menstruation is a natural phenomenon and an important indicator of women’s health reflecting their reproductive function. However data on experiences of menstruation and it’s impact on the health status, quality of life and social integration among women in developing countries is scanty. 75% of girls have one or more problems associated with menstruation. Methods: A cross sectional study was conducted to estimate the prevalence of menstrual problems among school going students in the age group of 12-17 years. 510 adolescent girls of randomly selected government schools in Thiruvananthapuram district were studied by a pretested semi structured questionnaire. Results: Mean age of menarche is 12.2. Out of 510 students 352 have normal menstrual cycles (50.1%). 10% have scanty menstruation, 31% have menorrhagia. Majority of girls (84.8%) has one or other menstrual problems. 33% of girls suffer from dysmenorrhea. Among 510 participants 31.6% reported that menstrual problems affects their daily life activities. 14.7% could not attend the class and 12.8% attend the class without taking medication but not participating in any outdoor activities. Conclusions: Menstrual problems are present in majority of girls in the study group which has some effect on the academic performance and other extracurricular activities in school.